Thiophene and diethylaminophenol-based "turn-on" fluorescence chemosensor for detection of Al3+ and F− in a near-perfect aqueous solution. Issue 18 (4th May 2017) - Jeong, Ha Young; Lee, Seong Youl; Han, Jiyeon; Lim, Mi Hee; Kim, Cheal
Abstract: A new fluorescent sensor1, based on thiophene and diethylaminophenol moieties, has been synthesized and its binding capabilities for metal-ion and anion recognition were investigated. The sensor1 showed 'turn-on' fluorescence in the presence of Al 3+ and F − . The sensing behaviors of1 with Al 3+ and F − were studied by using photophysical experiments, 1 H NMR titration, and ESI-mass spectrometry analysis. The detection limits for the analysis of Al 3+ and F − were found to be 0.41 μM and 14.36 μM, respectively, which are below the WHO guidelines for drinking water (7.41 μM for Al 3+ and 79 μM for F − ). Moreover, turn-on fluorescence of1 toward Al 3+ and F − caused by intramolecular charge transfer (ICT) was well explained by density functional theory (DFT) calculations. Importantly, 1 could be used to detect Al 3+ in the living cells. Graphical abstract: